2015
DOI: 10.4049/jimmunol.1400803
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s Tyrosine Kinase Synergizes with Notch2 To Govern Marginal Zone B Cells in Nonobese Diabetic Mice

Abstract: Expansion of autoimmune-prone marginal zone (MZ) B cells has been implicated in type 1 diabetes (T1D). To test disease contributions of MZ B cells in NOD mice, Notch2 haploinsufficiency (Notch2+/−) was introduced, but failed to eliminate the MZ, as it does in C57BL/6 mice. Notch2+/−/NOD have MZ B cell numbers similar to WT C57BL/6, yet still develop diabetes. To test whether BCR-signaling supports Notch2+/−/NOD MZ B cells, Bruton's tyrosine kinase (Btk)-deficiency was introduced. Surprisingly, MZ B cells faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This observation highlights the importance of physiologic models of tolerance compared with Tg expression of foreign proteins (13,(55)(56)(57). Previous work by our group shows that different insulin-binding populations are characterized by two predominant L chains (5,17,40). In V H 125 SD .NOD mice, distinct insulin-binding populations can also be visualized.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This observation highlights the importance of physiologic models of tolerance compared with Tg expression of foreign proteins (13,(55)(56)(57). Previous work by our group shows that different insulin-binding populations are characterized by two predominant L chains (5,17,40). In V H 125 SD .NOD mice, distinct insulin-binding populations can also be visualized.…”
Section: Discussionmentioning
confidence: 59%
“…Significantly increased frequencies of T2 and MZ B cells were observed in the insulin-binding B cells compared with non-insulin-binding B cells (p , 0.001 for each subset). Although anti-insulin B cells can enter all peripheral B cell compartments, they are enriched in the T2 and MZ subsets, which are recognized for their heightened responsiveness to innate signals and enhanced capacity for Ag presentation (23,(38)(39)(40). Conversely, the frequencies of FO B cells were significantly decreased in the insulin-binding population compared with noninsulin-binding B cells (p , 0.001).…”
Section: Immature Anti-insulin B Cells That Leave the Bone Marrow Sucmentioning
confidence: 99%
“…Anti-insulin B cells and autoantibodies were severely reduced, while total B cell numbers and total IgG levels were not (26, 37). We also showed that Btk supports naturally occurring autoreactive-prone anergic (An1) and autoreactive marginal zone (MZ) NOD B cells (26, 37, 91), which may also have implications for arthritis, as this subset was recently shown to be a primary source of anti-collagen B cells in collagen-induced arthritis (92). …”
Section: Introductionmentioning
confidence: 68%
“…Equally striking is the profound reduction of the marginal zone compartment, which began even at the pre-marginal zone stage. Although in most models the marginal zone develops independently of BTK, we recently reported that NOD mouse marginal zone B cells rely in part on BTK signals (44). Even in NOD mice, however, loss of BTK causes a block at the premarginal zone stage, with an increase in numbers, and only partial reduction of marginal zone B cells (4).…”
Section: Discussionmentioning
confidence: 99%